Ultrafiltration pretreatment enhances the flux, resilience and permeate quality from membrane distillation for water recovery from concentrated blackwater (urine/faeces) - Davey, Christopher J. (Cranfield University, 2020)
Underlying data for manuscript.
Keywords: Urine'; 'Faeces'; 'Sanitation'; 'Single-household'; 'Fouling'; 'Ammonia'; 'Membrane and Separation Technologies'